Spirulina sebagai Agen Kardioprotektif Potensial terhadap Dislipidemia Akibat Minyak Goreng Bekas: Studi Eksperimental dengan Wawasan Mekanistik: Spirulina sebagai Agen Kardioprotektif Potensial terhadap Dislipidemia Akibat Minyak Goreng Bekas: Studi Eksperimental dengan Wawasan Mekanistik - Royhanaty, Isy; Prayogo, Fitra Adi; Amelia, Poppy Fransisca; Elza, Stefani; Wijayanti, Eka Anita; Falasifah, Falasifah (Universitas Airlangga, 2026)
Background: Repeatedly heated cooking oil promotes dyslipidemia and oxidative stress, both major risk factors for cardiovascular disease. Spirulina platensis, a microalga rich in bioactive compounds, has been proposed as a protective agent against these effects. Objectives: This study evaluated the protective effects of Spirulina platensis on dyslipidemia and oxidative stress induced by repeatedly heated cooking oil in Wistar rats. Methods: Eighteen male Wistar rats (220–250 g) were divided into three groups (n=6): a negative control (standard diet), a positive control (standard diet plus heated cooking oil, 2 mL/rat/day), and a treatment group (heated oil plus spirulina, 330 mg/kg BW/day). After 28 days, total cholesterol, triglycerides, HDL-C, LDL-C, atherogenic index, MDA, GSH, and SOD were measured spectrophotometrically. Results: Compared with the positive control, spirulina lowered total cholesterol from 180.0±15.6 to 140.0±9.5 mg/dL (−22.2%, p-value<0.001), triglycerides from 150.0±18.7 to 100.0±10.3 mg/dL (−33.3%, p-value<0.001), and LDL-C from 120.0±16.8 to 80.0±8.7 mg/dL (−33.3%, p-value<0.001). HDL-C rose from 30.0±4.2 to 45.0±6.1 mg/dL (+50.0%, p-value<0.001), while the atherogenic index fell from 5.0±0.8 to 2.1±0.4 (−58.0%, p-value<0.001). Oxidative stress markers also improved: MDA decreased from 7.28±0.92 to 4.33±0.58 nmol/mL (−40.5%), GSH increased from 2.20±0.38 to 3.44±0.46 µmol/L (+56.4%), and SOD from 4.18±0.72 to 6.97±0.83 U/mL (+66.7%) (all p-value<0.001). Conclusions: Spirulina supplementation (330 mg/kg BW/day) significantly attenuated dyslipidemia and oxidative stress induced by repeatedly heated cooking oil, improving lipid parameters by 22–50% and antioxidant status by 40–67%. These findings suggest spirulina has cardioprotective potential against oxidized dietary fats.